'Fairy Chimney'‐Shaped Tandem Metamaterials as Double Resonance SERS Substrates. Issue 4 (12th October 2012) - Cinel, Neval A.; Bütün, Serkan; Ertaş, Gülay; Özbay, Ekmel
Abstract: A highly tunable design for obtaining double resonance substrates to be used in surface‐enhanced Raman spectroscopy is proposed. Tandem truncated nanocones composed of Au‐SiO2 ‐Au layers are designed, simulated and fabricated to obtain resonances at laser excitation and Stokes frequencies. Surface‐enhanced Raman scattering experiments are conducted to compare the enhancements obtained from double resonance substrates to those obtained from single resonance gold truncated nanocones. The best enhancement factor obtained using the new design is 3.86 × 10 7 . The resultant tandem structures are named after "Fairy Chimneys" rock formation in Cappadocia, Turkey. Abstract : A highly tunable design including tandem truncated nanocones composed of Au‐SiO2 ‐Au layers for obtaining double resonances at laser excitation and Stokes frequencies is proposed for use as substrates in surface‐enhanced Raman spectroscopy. Enhancements obtained from double resonance substrates to those obtained from single resonance substrates are compared.